Improving the Narrative Writing Skills Through the Picture and Picture Learning Model in 4th Grade Elementary School Students - Fitriani, Viona; Agustina, Tresia; Rahma, Sati; Sari, Rulia; Pebriana, Putri Hana (The Future of Education Journal, 2025)
This research focuses on the problem of students' low ability to write narrative essays. The aim of this research is to help students develop narrative writing skills by applying the PWIM (Picture Word Induction Model) learning model. This approach involves the use of an outline of the essay as well as proper use of capital letters and punctuation. The PWIM model is specifically designed to improve the narrative writing skills of students in class IV of SD Muhammadiyah 11 Mangkuyudan Surakarta in the 2024/2025 academic year. The research subjects consisted of 30 class IV students. Preliminary test results showed that only 2 students (9.09%) achieved the minimum integrity standard (KKM) of 66.7 in writing narrative texts, while 27 other students (90.91%) did not meet this standard. The research was conducted in three cycles and the tools used included observation, interviews, field notes and tests. Research findings show an increase in the aspects of main ideas, essay outlines, and the use of capital letters and full stops. Thus, it can be concluded that the application of the PWIM model effectively improves narrative writing skills in fourth grade students at SD Muhammadiyah 11 Mangkuyudan Surakarta.